2008
DOI: 10.1103/physrevb.78.235429
|View full text |Cite
|
Sign up to set email alerts
|

Charge-induced formation of linear Au clusters on thin MgO films: Scanning tunneling microscopy and density-functional theory study

Abstract: Gold deposition onto ultrathin MgO films on Ag͑001͒ results in the formation of linear Au clusters, as revealed from a combined scanning tunneling microscopy and density-functional theory study. The equilibrium structure of small Au clusters containing three to seven atoms is therefore different on thin film and bulk MgO͑001͒ but also deviates from the shape of the respective gas-phase clusters. The peculiar one-dimensional growth regime of gold is stimulated by an electron transfer from the MgO/Ag interface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(104 citation statements)
references
References 40 publications
7
96
0
1
Order By: Relevance
“…It has been observed that one-dimensional chains assemble spontaneously along the [001] direction of a thin alumina film deposited on a NiAl(110) surface; single-atom chains have been identified by imaging the surface after atom deposition [64,74]. A very similar phenomenon has been observed on top of an ultrathin MgO film deposited onto a Ag(001) surface [75]. Lifting single-atom chains requires an extremely accurate control of the manipulation process and also a significantly high stability of the system.…”
Section: From Freely Suspended Wires To Single-wires Lifted By Stmsupporting
confidence: 49%
See 2 more Smart Citations
“…It has been observed that one-dimensional chains assemble spontaneously along the [001] direction of a thin alumina film deposited on a NiAl(110) surface; single-atom chains have been identified by imaging the surface after atom deposition [64,74]. A very similar phenomenon has been observed on top of an ultrathin MgO film deposited onto a Ag(001) surface [75]. Lifting single-atom chains requires an extremely accurate control of the manipulation process and also a significantly high stability of the system.…”
Section: From Freely Suspended Wires To Single-wires Lifted By Stmsupporting
confidence: 49%
“…Similar experiments to the one described in Ref. have been performed a few years later using a thin (5 Å) insulating film deposited on a metallic surface as substrate to deposit single gold atoms [64,74,75]. It has been observed that one-dimensional chains assemble spontaneously along the [001] direction of a thin alumina film deposited on a NiAl(110) surface; single-atom chains have been identified by imaging the surface after atom deposition [64,74].…”
Section: From Freely Suspended Wires To Single-wires Lifted By Stmmentioning
confidence: 58%
See 1 more Smart Citation
“…They also exhibit a high tendency to accumulate excess charges that have been transferred from the support. 8,9 Finally, the cluster perimeter is easily accessible for mobile reactants that either diffuse on the metal aggregate or migrate on the oxide surface. This proximity of metal and oxide binding sites renders the periphery atoms ideal candidates to sustain chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The large modifications in adsorption owing to the metal support are not limited to Au or other transition metal single atoms, but significant changes are also seen in Au cluster geometries, charge states, and adsorption energies on metal-supported MgO films [107][108][109][110][111] . For comparison, on bulk MgO the smallest Au N (N=2-6) clusters favour minimal wetting with 14 one or two Au atoms in contact with oxide ions 28,94,108,112,113 .…”
Section: Preparation and Properties Of Modified Simple Oxidesmentioning
confidence: 99%